Respons Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) terhadap POC Urine Sapi dan Pupuk Urea di Pembibitan Awal pada Media Gambut - Butar, Robert Raikes Manalu R; Sabli, T. Edy (Jurnal Agroteknologi, Agribisnis, dan Akuakultur, 2026)
This study aims to determine the interaction effect and the main effect of LOF (liquid organic fertilizer) of cow urine and urea fertilizer. This research was conducted at the Experimental Garden of the Faculty of Agriculture, Islamic University of Riau, started from November to February 2023. This research used a completely randomized design (CRD) in factorial which consisted of two factors. The first factor was the LOF concentration of cow urine which consisted of 3 treatment levels, namely: 75, 150 and 225 ml/l of water. The second factor was the dose of urea fertilizer which consisted of 5 treatment levels, namely: 0, 1.5, 3, 4.5 and 6 g/polybag. Each treatment consisted of 3 replications so that there were 45 experimental units. Parameters observed were plant height, number of fronds, length of fronds, stem diameter, root volume and root length. The data were analyzed statistically and continued with the honest significant difference test (BNJ) at the 5% level. The results showed that the interaction effect of cow urine LOF and urea fertilizer was not significantly different on the parameters of plant height, number of fronds, frond length and stem diameter. The main effect of LOF of cow urine was significantly different on all observation parameters with the best treatment at a concentration of 225 ml/l water (S3). The main effect of urea fertilizer was significantly different on all observation parameters with the best treatment at a dose of 4.5 g/polybag (U3).